A heart-on-a-chip platform for online monitoring of contractile behavior via digital image processing and piezoelectric sensing technique. (January 2020) - Sakamiya, Mutsuhito; Fang, Yongcong; Mo, Xingwu; Shen, Junying; Zhang, Ting
Highlights: l A heart-on-a-chip platform with online monitoring of contractile behavior for 3D cardiac tissue constructs was developed via an image processing system and a piezoelectric sensing system at the same time. l The image processing system measured the deformation of micro-pillar array during contraction and offered in situ multi-site detection of contractile behavior. l The piezoelectric sensing system provided the contractile behavior of the entire cardiac tissues by measuring the stresses exerted on the PVDF film due to the deformation of pillars. l The results demonstrated that this heart-on-a-chip platform had potential use in cardio-related drug screening application. Abstract: Heart-on-a-chip devices have recently emerged as a viable and promising model for drug screening applications, owing to its capability of capturing important biological and physiological parameters of cardiac tissue. However, most heart-on-a-chips are not developed for online and continuous monitoring of contractile behavior, which are the main functional characteristics of cardiac tissue. In this study, we designed and investigated on a heart-on-a-chip platform that provides online monitoring of contractile behavior of a 3D cardiac tissue construct. The contractile behavior include contraction force, frequency, and synchronization. They can be evaluated by an image processing system and a piezoelectric sensing system simultaneously. Based on the deformation of a micro-pillar array embedded within the 3D cardiac tissue upon subjected to cardiac contraction, the image processing system provides in situ multi-site detection of the contractile behavior. At the same time, the piezoelectric sensing system measures the contractile behavior of the entire cardiac tissue construct. A 3D cardiac tissue construct was successfully fabricated. Then the heart-on-a-chip platform was validated by applying various motion patterns on the micro-pillars, which mimicked the contraction patterns of the 3D cardiac tissue. The drug reactivity of the 3D cardiac tissue construct after a treatment of isoproterenol and doxorubicin was evaluated by measuring the contractile behavior via the image processing and the piezoelectric sensing systems. The results from the drug reactivity provided by both these measurement systems were consistent with previous reports, demonstrating the reliability of the heart-on-a-chip platform and its potential for use in cardio-related drug screening applications.